Optimizing Container Loading With Autonomous Robots - Stavrou, Demetris; Timotheou, Stelios; Panayiotou, Christos G.; Polycarpou, Marios M. (IEEE transactions on automation science and engineering, 2018)
In this paper, we investigate a problem associated with transferring a set of containers from the storage to the loading area of a warehouse using autonomous robots. In addition to assigning robots to containers, the special topology considered in this paper requires coordinated planning of the robots' movement to avoid conflicts. We formulate the joint problem of robot assignment and movement coordination with the objective of minimizing the time required for all robots to carry their assigned containers to the destination, subject to conflict-free movement of all robots. We use the concept of abstract time windows (ATWs) to represent the movement of robots. The conditions for detecting conflicts in the ATW representation are introduced along with the necessary operations for resolving conflicts. For the solution of the problem, two approaches are developed. The first is a mathematical programming approach that formulates the problem as a mixed-integer linear program that allows optimal solution using appropriate solvers, while the second is a heuristic approach that allows fast, close-to-optimal solutions. Even though the proposed approaches focus on the case where the number of robots is equal to the number of containers, we also discuss how to solve the problem when having unequal number of robots and containers. Simulation results show that the heuristic approach provides a solution within 5% of the optimal solution with the minimum time of completion of all tasks being the performance metric, and executes six orders of magnitude faster than a state-of-the-art mathematical programming solver. Note to Practitioners -Robotic systems are increasingly used in logistics facilities, such as warehouses and container terminals. Nonetheless, achieving improved efficiency in this context poses several challenges in terms of real-time execution, coordinated resolution of robot conflicts, and adaptation to unpredictable events in operational environments. This paper examines a problem related to the coordination of a team of autonomous robots operating in a container handling facility, where containers need to be transferred from the storage area to a loading station. The considered topology involves containers arranged in lanes for efficient storage, but imposes limitations on the movement of autonomous robots. Such a topology is commonly found in container terminals where straddle carriers have to transfer containers from a storage yard to quay cranes or trucks and vice versa, but have limitations on moving on the same or even adjacent container lanes. To address this problem, we develop a novel method that efficiently assigns containers to robots and defines appropriate timings for collective coordination of robot movements. We illustrate that the proposed method provides very efficient results (within 5% from the optimal) for multiple configuration scenarios. Even more importantly, the method is suitable for real-time execution as it solves problems with hundreds of robots/containers within a few milliseconds; this further offers the ability for solution adaptation in dynamically varying environments, e.g., in situations of robot delays or breakdowns.